Inhibition of nitric oxide production and free radical scavenging activities of four South African medicinal plants - Adebayo SA; Ondua M; Shai LJ; Lebelo SL (Dove Medical Press, 2019)
SA Adebayo,1,2 M Ondua,3 LJ Shai,2 SL Lebelo41Phytomedicine and Phytopharmacology Research Group, Department of Plant Sciences, University of the Free State, Phuthaditjhaba 9866, South Africa; 2Department of Biomedical Sciences, Faculty of Science, Tshwane University of Technology, Pretoria 0001, South Africa; 3Department of Paraclinical Sciences, Faculty of Veterinary Science, University of Pretoria, Onderstepoort 0110, South Africa; 4Department of Life and Consumer Sciences, University of South Africa, Florida 1710, South AfricaIntroduction: Traditional healing is often the preferred form of therapy especially in rural and resource-limited communities. The extracts of plants are used to treat many diseases such as arthritis and chronic pain. Four medicinal plant species, namely, Acokanthera oppositifolia, Plantago lanceolata, Conyza canadensis and Artemisia vulgaris used in Southern Africa to treat pain and inflammation-related diseases were selected for evaluation in laboratory-based experiments.Methods: The selected plant species were evaluated for phytochemical content, antioxidant and anti-inflammatory activities, as well as cytotoxicity effects against mammalian cells in culture.Results: The results indicated that the n-hexane and chloroform extracts of P. lanceolata had the best antioxidant activities with an IC50=0.41 μg/mL. Also, the acetone extracts of P. lanceolata had 93.76% nitric oxide (NO) inhibition. However, the chloroform and n-hexane extracts of C. canadensis produced NO inhibition of 98.53% and 99.2%, respectively, at 100 μg/mL with IC50=17.69 μg/mL. Furthermore, the ethyl acetate extracts also had promising NO inhibitory activity (96.33%), but the cytotoxicity results with cell viabilities of 5.31%, 5.7% and 5.89%, respectively, suggested that the observed activity was due to a cytotoxic effect. Acetone extracts of C. canadensis were also cytotoxic at 30 μg/mL with 6.07–6.67% cell viabilities compared with the acetone extracts of P. lanceolata (99.57%).Conclusion: The results partially validate the ethnomedicinal uses of the selected plant species used for inflammation-related conditions. However, because some of the extracts had potential cytotoxic effects, caution is advised in their use, especially those consumed orally.Keywords: nitric oxide, free radicals, medicinal plants, South Africa, inflammation